Use the quotient rule to find the derivative?

#f(x)=((4x-1)(3x^2+1))/(5x+2)#

#f(x)=((4x-1)(3x^2+1))/(5x+2)#

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

1
Mar 8, 2018

Answer:

#d/dx(g(x)/(h(x))) = (g'(x)*h(x) - h'(x)*g(x))/(h^2(x))#

Explanation:

Using the quotient rule,
we get #g(x) = (4x-1)(3x^2+1)# and #h(x) = 5x+2#

#g'(x) = 4(3x^2+1) + 6x(4x-1)#
#h'(x) = 5#

#d/dxf(x) = ((4(3x^2+1) + 6x(4x-1))(5x+2) - 5(4x-1)(3x^2+1))/(5x+2)^2#

#=> (120 x^3 + 57 x^2 - 12 x + 13)/(5 x + 2)^2#

Was this helpful? Let the contributor know!
1500